DESIGNING MULTIPLE CHOICE TEST OF VOCABULARY FOR THE FIRST SEMESTER STUDENTS AT ENGLISH EDUCATION DEPARTMENT OF ALAUDDIN STATE ISLAMIC UNIVERSITY OF MAKASSAR - Raidah Mahirah; Djuwairiah Ahmad; Sukirman , (Universitas Islam Negeri Alauddin Makassar, 2016)
This study aims to develop and design Vocabulary Test in the first semester students at English Education Department of Alauddin State Islamic University of Makassar. The research design was Research and Development (R&D). It totally applied ADDIE Model. The steps of the model are Analysis, Design, Develop, Implementation and Evaluation. The type of data of this research was quantitative data. The research instrument was a rubric dealing the quality of the test produced. The findings showed that the content of material, language, and layout of the product were totally clear and understandable. The product was valid to be implemented in testing the students’ vocabulary mastery. It can be seen fromthe difficulty level, discrimination power, validity, and reliability of the product obtained from the score of the students’ answers.